Infrastructure systems mechanics, design, and analysis of components - Fertis, Demeter G. (Wiley series in infrastructure management and design., 1997)
A comprehensive foundation in infrastructure design and analysis. Infrastructure Systems offers complete coverage of both static and dynamic analysis and design of infrastructure systems, from the basics of structural mechanics and dynamics to advanced analysis techniques. Bridging theory and applications, this invaluable book contains unique methods that simplify the analysis and design of nonlinear and complex linear infrastructural systems -powerful new tools for both informed students and practicing engineers. Well-written and easy to follow, Infrastructure Systems presents: * Fundamentals of statics, stress and deformation, and infrastructural dynamics of beams, frames, buildings, bridges, and other components * Equivalent systems, infrastructural nonlinearities, instability, and inelastic response for components of uniform or variable stiffness * A detailed examination of structures subjected to earthquake excitations and blast loadings -elastic and elastoplastic analyses, Lagrange's equation, and more * Energy concepts and applications, and the finite element and finite difference methods * Extensive examples and illustrations, plus detailed answers to selected problems.